Homeostase do cálcio e marcadores do metabolismo ósseo no hipertireoidismo felino - Revisão - Cardoso, M. J L; Muniz, L. M R [UNESP]; Gasparini, T. J.; Melussi, M. (My University, 2007)
Hyperthyroidism is the most frequent endocrine disease in old-aged cats. It is a illness provoked by the excess of circulating thyroid hormones. Hyperthyroidism causes alteration in bone metabolism with predominance of activity resorption. The evaluation of bone metabolism can be made by measuring serum and urinary markers of bone metabolism or bone mineral densitometry. Osteoblasts are responsible cells for bone formation while the osteoclasts are for resorption. In physiological situation osteoblastic and osteoclastic activities are in balance. Markers of bone formation express the osteoblastic activity and markers of the osseous resorption the osteoclástica activity. Markers of bone turnover are important in the diagnosis and prognostic of muscle-skeletal disease, as well as in the accompaniment of therapy. It is fundamental do carry on studies on the influence of feline hyperthyroidism on markers of bone formation and resorption in bone turnover to comprise pathophysiologic mechanism of bone alterations.
Calcium homestasis markers of bone metabolism in feline hyperthyroidism - A review
Keywords: Cats; ICTP; Osteocalcin; Thyroid; Thyroxine; Felidae